2005
DOI: 10.1111/j.1365-2664.2005.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Questionnaires in ecology: a review of past use and recommendations for best practice

Abstract: Summary 1.Questionnaires, or social surveys, are used increasingly as a means of collecting data in ecology. We present a critical review of their use and give recommendations for good practice. 2. We searched for papers in which questionnaires were used in 57 ecological academic journals, published over the period [1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003] inclusive. This provided a total sample size of 168 questionnaires from 127 papers published in 22 academic journals. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(233 citation statements)
references
References 52 publications
5
215
1
3
Order By: Relevance
“…This approach is increasingly being used by ecologists to investigate changes in ecological systems associated with human behavior (White et al 2005). Rapid assessment interviews with local people are relatively inexpensive and provide reliable information on resource trends (Jones et al 2008).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…This approach is increasingly being used by ecologists to investigate changes in ecological systems associated with human behavior (White et al 2005). Rapid assessment interviews with local people are relatively inexpensive and provide reliable information on resource trends (Jones et al 2008).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Before land management policies are instituted, officials in charge of environmental regulations are increasingly seeking to understand public perception, not only for consultation but also to augment the education of the public on human-wildlife conflict (White et al, 2005). Other surveys have shown that people express concern about the environment, but only rarely do they act on these concerns (Kaiser, Ranney, Hartig & Bowler, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to understand how research-based management actions may influence tourist perceptions and attitudes. Collecting human survey data has become increasingly popular (White, Jennings, Renwick, & Barker, 2005), and rapid human dimension developments have been made to better understand human-wildlife conflict ("Human", 2013). All of those involved have a view point to be recognized.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Questionaires are suitable tools to unravel public perceptions in ecological management (White et al 2005), and have been successfully used to assess perceptions and attitudes toward the biota in Chile (e.g., Muñoz-Pedreros et al 2000, De la Fuente et al 2004 as examples of other survey-based studies).…”
Section: Surveymentioning
confidence: 99%